Nuclear factor erythroid 2 – related factor 2 and its relationship with cellular response in nickel exposure: a systems biology analysis (2019)
Background: Nickel and nickel-containing compounds (NCC) are known human carcinogens. However, the precise molecular mechanisms of nickel-induced malignant transformation remain unknown. Proposed mechanisms suggest that nickel and NCC may participate in the dual activation/inactivation of enzymatic pathways involved in cell defenses against oxidative damage, where Nuclear factor-erythroid 2 related factor 2 (Nrf2) plays a central role. Methods: For assessing the potential role of proteins involved in the Nrf2-mediated response to nickel and NCC exposure, we designed an interactome network using the STITCH search engine version 5.0 and the STRING software 10.0. The major NCC-protein interactome (NCPI) generated was analyzed using the MCODE plugin, version 1.5.1 for the detection of interaction modules or subnetworks. Main centralities of the NCPI were determined with the CentiScape 2.2 plugin of Cytoscape 3.4.0 and main biological processes associated with each cluster were assessed using the BiNGO plugin of Cytoscape 3.4.0. Results: Water-soluble NiSO4 and insoluble Ni3S2 were the most connected to proteins involved in the NCPI network. Nfr2 was detected as one of the most relevant proteins in the network, participating in several multifunctional protein complexes in clusters 1, 2, 3 and 5. Ontological analysis of cluster 3 revealed several processes related to unfolded protein response (UPR) and response to endoplasmic reticulum (ER) stress. Conclusions: Cellular response to NCC exposure was very comparable, particularly concerning oxidative stress response, inflammation, cell cycle/proliferation, and apoptosis. In this cellular response, Nfr2 was highly centralized and participated in several multifunctional protein complexes, including several related to ER-stress. These results add evidence on the possible Ni2+ induced – ER stress mainly associated with insoluble NCC. In this scenario, we also show how protein degradation mediated by ubiquitination seems to play key roles in cellular responses to Ni.